Battue ou chasse à courre, en Somalie ou en Asie - Eric Frécon (EchoGéo)
Since last August, there were markedly more attacks registered off the Horn of Africa. The lack of coordination between the numerous initiatives is making surveillance operations inefficient. Further in the east, the littoral States along the Malacca Straits have managed to expel the pirates. Nevertheless, this success – often showed as an example – is not total. Moreover, it is not only due to the sea and air patrols.